2020
DOI: 10.21203/rs.3.rs-25090/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aboriginal Community Controlled Health Organisations address health equity through action on the social determinants of health of Aboriginal and Torres Strait Islander peoples in Australia.

Abstract: Background Indigenous populations globally are continually striving for better health and wellbeing due to experiencing significant health and social inequities. The social determinants of health are important contributors to health outcomes. Comprehensive primary health care that is governed and delivered by Indigenous people extends beyond the biomedical model of care to address the social determinants of health. Aboriginal Community Controlled Health Organisations (ACCHOs) are known to provide culturally in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…For Indigenous peoples—and any community that has suffered from colonization and imperialism—settler colonialism and racism are intertwined. Although Indigenous peoples consistently identify colonialism as being one of the most significant determinants of their health and well‐being, it is not typically accounted for as such in academic literature or in western healthcare praxis (Greenwood et al, 2018; Reading & Wien, 2009). The refusal of western healthcare to engage with the myriad impacts of settler colonialism and systemic racism on Indigenous health and well‐being makes it obvious that these systems have never and will never be able to adequately prevent or treat widespread illness or support the healing of Indigenous communities and people (Rowe et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For Indigenous peoples—and any community that has suffered from colonization and imperialism—settler colonialism and racism are intertwined. Although Indigenous peoples consistently identify colonialism as being one of the most significant determinants of their health and well‐being, it is not typically accounted for as such in academic literature or in western healthcare praxis (Greenwood et al, 2018; Reading & Wien, 2009). The refusal of western healthcare to engage with the myriad impacts of settler colonialism and systemic racism on Indigenous health and well‐being makes it obvious that these systems have never and will never be able to adequately prevent or treat widespread illness or support the healing of Indigenous communities and people (Rowe et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Consultations with ACCHOs have highlighted key principles which inform holistic approaches to the social determinants of health including self-determination, accessible and culturally safe care and strong partnerships that support clients to navigate social services (CREATE, 2020). A recent document analysis of 67 ACCHO annual reports found that all services were working to improve clients' intermediary social determinants of health, specifically material circumstances, biological, behavioural and psychosocial factors (Pearson et al, 2020). Whilst structured and funded Aboriginal and Torres Strait Islander health assessments for preventative care are widely implemented, these assessments are limited by a biomedical focus that inadequately addresses social and cultural factors (Bailie et al, 2019).…”
Section: Introductionmentioning
confidence: 99%